Dermatological concerns for women and girls with turner syndrome - Rodriguez-Buritica, David; Mones, Meaghan; Prakash, Siddharth K.; Rivera, Michelle; Aldrich, Melissa; Rogge, Megan; Richardson, Kate (Frontiers in Medicine, 2023)
IIntroduction: Turner syndrome (TS) is associated with distinct manifestations in women and girls including short stature, cardiac abnormalities, premature ovarian failure as well as dermatological features, including lymphedema, keloids, onychodystrophy, and acne. Although many dermatological concerns present during the first few decades of life, the overwhelming majority of respondents are not provided with dermatology referrals at diagnosis. Methods: This cross-sectional study utilized an author designed survey to assess self-reported dermatological manifestations, dermatology referral experience, common therapies for select dermatological conditions, as well as a validated 10-question Dermatology Life Quality Index (DLQI) to assess quality-of-life impact in women and girls with Turner syndrome. Results: In our cohort, 64% (n=149) had been referred to a dermatologist at some point in their life time. The majority of individuals self-identified their dermatological concern (79.6%) and were referred after a dermatological concern had already occurred (90.2%). The most common dermatological findings reported were xerosis cutis (78.7%), lymphedema (73%), and more than 20 acquired melanocytic nevi (70%). The overall mean DLQI score was 3.52, indicative of a small effect on the patient's life. Onychodystrophy, history of skin biopsy, and lymphedema were statistically significant to have a higher impact on quality of life. Discussion: Our data reveal that skin conditions are highly prevalent in the TS population during the early decades of life and affirm utilizing these conditions in the TS diagnostic process, as well as emphasize the need for specialized dermatology referrals to address the detrimental impacts related to skin concerns on quality of life.